Catalytic α-Oxidation of N-Acylated 1,3-Oxazolidin-2-ones with Molecular Oxygen - Sundman,Tanja (2026)
Introduction: Molecular oxygen is the most common oxidizer in nature. Since it has been part of evolution, it is heavily incorporated into biological systems, the most significant being cellular respiration, glycolysis, and the citric acid cycle. Luckily, molecular oxygen can also be used as an oxidizer in the lab, and with the right conditions, to generate 1,2-dicarbonyl compounds. Background: Given that many proteins have developed an affinity for this type of compound, several pharmaceuticals have been made with this functionality, to increase their bioavailability. Examples are Indibulin, Biricodar, Boceprevir, and Fluocortin butyl. Aim: The aim is to investigate if N-acylated 1,3-oxazolidin-2-ones can be catalytically and selectively α-oxidized by non-harmful and abundant molecular oxygen via an in-situ formed copper(II) complex with a high tolerance for a wide range of aromatic substrates, and to explore how different nitrogen-based ligands affect this reaction. Methods: To connect the methodology to more common starting materials, some of the substrates will also be synthesized from 1,3-oxazolidin-2-one and the corresponding carboxylic acid via the formation of a mixed anhydride. An objective is to fully characterize the corresponding oxidated products by 1H NMR spectroscopy, 13C NMR spectroscopy, FTIR spectroscopy, melting point, and HRMS. Results: The reaction showed a high tolerance for a wide range of aromatic N-acylated 1,3 oxazolidin-2-ones, with a few exceptions where optimization is needed. A ligand screening revealed that 1,10-phenanthroline was the best choice of ligand out of eleven tested. Conclusion: The reaction is a good synthetic pathway to generate 1,2-dicarbonyl compounds, and has also proven to be green due to its conditions and atom economy.
Keywords: 1; 2-dicarbonyl compounds; molecular oxygen; scaffold; metal enolate; catalysis; organic chemistry